Envolvimento de PGE2 na diferenciação de células Th17 in vivo pela fagocitose de células apoptóticas infectadas - Dias, Fernanda De Nuzzi [UNESP] (2015)
The phagocytosis of infected-apoptotic cells (iAC) by dendritic cells (DC) induces the production of TGF-β, IL-6 and IL-23, providing a microenvironment to Th17 cell differentiation. Recent data obtained in our group showed that the phagocytosis of infected- apoptotic cells by CD also results in high levels of IL-1β and PGE2. The presence of these soluble mediators was able to induce the differentiation of Th17 cells, in vitro. However, the inhibition of PGE2 synthesis, by non-selective COX inhibitor (indomethacin), result the increase of percentage of Th17. In this study, it was evaluated the effect of phagocytosis of infected-apoptotic cells (AC+E. coli) during the Th17 cell differentiation, in vivo, and the effect of PGE2 in this process. The inoculation of AC+ Ec (in.) into lung induced the production of IL-6, IL-1β and TGF-β in lung, suggesting that the presence of AC+Ec is able to induce a microenvironment favorable to Th17 cell differentiation. The instillation of AC+Ec induced the differentiation of Th17 cells. However, the treatment of the animals with COX inhibitor resulted in an increase in the percentage, and number, of Th17 cells in the lung. The presence of these cells increased in the percentage of neutrophils in the lung and that apparently reflect in bacterial clearance from the lung, compared to animals that received no treatment. Taken all together, the phagocytosis of AC+Ec promotes the Th17 cell differentiation. However, the production of PGE2 by efferocytosis suppresses the differentiation and / or migration of Th17 cells to the lungs, impair the recruitment of neutrophils and increase the susceptibility to lung infections.